Production of Syngas from Ethanol CO2 Reforming on La-doped Cu/Al 2O3: Impact of Promoter Loading - Nor Shafiqah, Mohd Nasir; Nguyen, Trinh Duy; Jun, Lau N.; Mahadi, Bahari; Pham, T. T. Phuong; Bawadi, Abdullah; Vo, Dai-Viet N. (2018)
Incipient wetness impregnation (IWI) method was applied to prepared 10%Cu/Al 2 O 3 whereas M%La-doped 10%Cu/Al 2 O 3 (Mwt%= 1%, 2%, 3%, 4% and 5%) were synthesized by employing sequential IWI technique. The prepared catalysts were evaluated from ethanol CO 2 reforming (ECR) at 1023 K and stoichiometric feed ratio. Average crystallite size of CuO particle is reduced with La-promoter addition probably caused by lanthana dilution effect that prevent agglomeration from occur within CuO particles. H 2 reduction process produce complete CuO reduction and constant signal is appear beyond 525 K suggests that the catalysts were completely reduced beyond that temperature. 3%La catalyst identified as optimal promoter loading based on reactant conversions. C 2 H 5 OH and CO 2 conversions were achieved on 3%La loading is 87.6% and 55.1%, respectively. Carbon was identified on catalyst surface based on X-ray diffraction (XRD) and scanning electron microscopy (SEM).